Analysis of the Impact of Delayed Chronic Drug Claims on Hospital Healthcare Service Quality: Systematic Literature Review - Rr. Devi Noviana Setyoningsih; Cahya Tri Purnami; Antono Suryoputro (PROMOTOR, 2026)
Delays in submitting reimbursement claims for chronic drug result in deferred payments, adversely affecting hospital cash flow. This financial strain leads to delays in employee compensation and challenges in ensuring adequate chronic drug availability for patients. This study aims to analyze how chronic drug claim processing delays impact the quality of healthcare services delivered by hospitals. This study utilizes a systematic literature review methodology, searching the PubMed, Scopus, and Google Scholar databases for publications from 2015-2025. The search strategy employs the following keywords: "chronic drug claims delay," "healthcare service quality," "chronic medication reimbursement," "hospital cash flow," and "pharmaceutical claims processing." The literature selection process follows the PRISMA guidelines. Based on the analysis of six selected articles, this study identifies the multidimensional impact of delayed chronic drug claims on hospital healthcare service quality across four key dimensions: Competency Dimension:delayed claims create hospital revenue instability, which adversely affects funding for human resource development and staff competency training programs. Service Effectiveness Dimension: claim processing delays necessitate changes in hospital budget allocation and strategic planning policies, resulting in suboptimal service delivery. Safety Dimension:delayed reimbursements lead to medication shortages, causing delays in providing essential chronic medications to patients and potentially compromising patient safety. Service Comfort Dimension:claims processing delays negatively impact pharmaceutical inventory management, affecting medication availability and overall patient comfort during treatment. Conclusion: Based on the analysis of six research articles published between 2015-2025, delayed chronic drug claims significantly impact hospital healthcare service quality across multiple dimensions, including competency, service effectiveness, safety, and service comfort.